Integrating Sustainable Digital Marketing Into MSMEs - Efendri Waruwu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to explore the dynamics involved in integrating sustainable digital marketing practices into Micro, Small, and Medium Enterprises (MSMEs). Employing a qualitative approach, the study adopts a mixed-method model combining interviews and case studies. The sampling technique involves purposive sampling to select participants representing diverse MSMEs. Data analysis utilizes thematic analysis to identify patterns and themes. The findings reveal a multifaceted understanding of sustainable digital marketing integration, highlighting challenges, opportunities, and best practices within MSMEs. Insights garnered from this research contribute to a deeper comprehension of sustainable digital marketing strategies tailored for MSMEs, thereby fostering their resilience and competitiveness in contemporary markets.